Hubungan antara Efikasi Diri dan Regulasi Diri dengan Prestasi Akademik pada Mahasiswa Program Studi Ilmu Al-Qur’an dan Tafsir UIN Raden Intan Lampung - Agustina, Fitri; Malay, Muhammad Nursalim (ANFUSINA: Journal of Psychology, 2019)
Academic achievement is an achievement achieved by someone in the academic field. This achievement can be achieved if a person has confidence and has the ability to manage him/her-self. This study aims to determine the relationship between self-efficacy and self-regulation with academic achievement in 57 students of the Al-Qur'an Science study program and the interpretation of UIN Raden Intan Lampung. The sampling technique used is sampling total then analyzed by multiple regression analysis techniques. The results of this research analysis explain that there is a relationship between self-efficacy and self-regulation with academic achievement in students of the study program of the Qur'an and the interpretation of UIN Raden Intan Lampung with a correlation coefficient (R) = 0,859 and F = 76,136 with p = 0,000. Then, there is a significant relationship between self-efficacy and academic achievement in students, the results of the analysis obtained are with the value of rx1y = 0,817 with p = 0,000. Furthermore, there is a relationship between self-regulation and academic achievement in students seen from the results of calculations obtained by the value rx2y = 0,854 with p = 0,000.